Persistence of High Levels of Serum Complement C5a in Severe COVID-19 Cases After Hospital Discharge - Senent, Yaiza; Inogés, Susana; López-Díaz de Cerio, Ascensión; Blanco, Andres; Campo, Arantxa; Carmona-Torre, Francisco; Sunsundegui, Patricia; González-Martín, Antonio; Ajona, Daniel; Okrój, Marcin; Prósper, Felipe; Pio, Ruben; et al. (Frontiers in Immunology, 2021)
Evidence supports a role of complement anaphylatoxin C5a in the pathophysiology of COVID-19. However, information about the evolution and impact of C5a levels after hospital discharge is lacking. We analyzed the association between circulating C5a levels and the clinical evolution of hospitalized patients infected with SARS-CoV-2. Serum C5a levels were determined in 33 hospitalized and 17 non-hospitalized patients from Clinica Universidad de Navarra. One hundred and ninety-two serial samples were collected during the hospitalization stay and up to three months during the follow-up. Median C5a levels were 27.29 ng/ml (25th to 75th percentile: 17.92-34.83) for samples collected during hospitalization, versus 16.76 ng/ml (12.90-25.08) for samples collected during the follow-up (p<0.001). There was a negative correlation between serum C5a levels and the number of days from symptom onset (p<0.001). C5a levels also correlated with a previously validated COVID risk score (p=0.012), and was associated with the severity of the disease (p<0.001). An overall reduction of C5a levels was observed after hospital discharge. However, elevated C5a levels persisted in those patients with high COVID-19 severity (i.e. those with a longest stay in the hospital), even after months from hospital discharge (p=0.020). Moreover, high C5a levels appeared to be associated with the presence of long-term respiratory symptoms (p=0.004). In conclusion, serum C5a levels remain high in severe cases of COVID-19, and are associated with the presence of respiratory symptoms after hospital discharge. These results suggest a role for C5a in the long-term effects of COVID-19 infection.